Bacterial strategies for suppression and evasion of plant immunity: Molecular and cellular aspects - Patyka, M. V.; Khablak, S. H.; Bondareva, L. M.; Patyka, T. I.; Dolia, M. M.; Spychak, V. M.; Lykholat, Y. V. (Regulatory Mechanisms in Biosystems, 2025)
The review analyzes current data on the molecular mechanisms employed by bacteria to suppress and evade plant defense responses. It presents the strategies used by various pathogenic bacteria to overcome protective barriers associated with the cell wall and cytoplasmic components, including the cytoskeleton, which play a crucial role in plant immune responses to pathogens. Particular attention is given to bacterial effector proteins translocated into plant cells via the Type III Secretion System (T3SS), aimed at suppressing plant innate immunity and interfering with additional defense-related cellular processes such as proteasome-mediated protein degradation, phytohormone signaling, c y toskeleton organization, vesicular trafficking, and gene expression. Promising chemical compounds and innovative strategies for the control of bacterial plant diseases are also discussed.